Clinical prediction methods as a learning tool in medical education - Sviatenko, Tetiana; Gogunska, Inna; Prockopets, Kostyantyn; Moroziuk, Olga; Dub, Natalia (Perspectivas em Diálogo: Revista de Educação e Sociedade, 2026)
The relevance of the study is determined by the need to develop the ability of medical students to make clinical prediction as a key component of professional thinking. The aim is to develop and evaluate the effectiveness of a training module on methods for predicting treatment outcomes in the training of future doctors. Research methods: modified Objective Structured Clinical Examination (OSCE), Clinical Reasoning Test, analytical test Medical Logic, self-assessment questionnaire, semi-structured group interview. As a result, the experimental group (EG) students (n=50) demonstrated significantly higher indicators on all criteria compared to the control group (CG) (n=50): Clinical Reasoning Test – 7.8 versus 5.1 points; OSCE – 8.3 versus 5.5; analytical thinking – 26.1 versus 19.2 points; improved self-esteem – up to +2.2 points. The training module turned out to be effective for the development of clinical reasoning, decision logic, and professional confidence. The academic novelty of the study is the first-ever approved integration of clinical prediction scales (CHA₂DS₂-VASc, SHFM, APACHE II, etc.) as a didactic tool in the Clinical Reasoning course. The prospects for future research is scaling up the module for interdisciplinary training, as well as in studying its impact on real clinical decisions of interns.